Kajian Perubahan Bioekologi pada Restorasi Ekosistem Mangrove di Segara Anakan Cilacap - Erwin Riyanto Ardli; Ani Widyastuti; Edy Yani (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Mangroves are coastal ecosystems that have a very large role for humans and ecosystems in the vicinity. Mangrove condition in Indonesia, including in Segara Chicks Cilacap experiencing enormous pressure resulting in damage to the mangrove ecosystem. Mangrove restoration is the process of return of mangrove ecosystems of the conditions are broken into previously conditioned as well. The general objective of this study was 1) determine the conditions and amendments BioEkologi mangrove ecosystem restoration in the area of results Segara Chicks. Specific objectives in the study the first year is to determine: 1) the community structure of mangrove ecosystems (vegetation and fauna associations) at a restoration site in the region Segara Chicks, 2) the spatial variation community mangrove ecosystem in the area of restoration, and 3) the condition of the environmental factors that support the mangrove restoration in the region Segara Chicks. The method used was survey method with the technique of sampling cluster random sampling. The data obtained were analyzed multivatiate covering biodiversity analysis, cluster analysis, multi-dimensional sclae (MDS), and Bio-env using PRIMER-E program. The study shows the restoration of mangrove vegetation in the region have relatively low diversity (H '<1), and in areas that have not been restored only dominated shrub species (Acanthus and Derris). Environmental factors generally favor mangrove Vegetasia life, and have the same tendency for each restoration location with a level of similarity> 95%.